2021
DOI: 10.3390/cells10071599
|View full text |Cite
|
Sign up to set email alerts
|

Fe65: A Scaffolding Protein of Actin Regulators

Abstract: The scaffolding protein family Fe65, composed of Fe65, Fe65L1, and Fe65L2, was identified as an interaction partner of the amyloid precursor protein (APP), which plays a key function in Alzheimer’s disease. All three Fe65 family members possess three highly conserved interaction domains, forming complexes with diverse binding partners that can be assigned to different cellular functions, such as transactivation of genes in the nucleus, modulation of calcium homeostasis and lipid metabolism, and regulation of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 276 publications
(412 reference statements)
0
11
0
Order By: Relevance
“…Of note, the level of calcium transporter SERCA2 is increased in FE65/FE65L1 double KO mice which suggest a role of FE65 in calcium homeostasis [ 42 ]. On the other hand, both ARF6 signalling and FE65 have been associated with lipid metabolism through the regulation of lipid-modifying enzymes [ 43 , 44 ] and binding to the low-density lipoprotein receptor family proteins [ 3 ], respectively. As aberrant calcium homeostasis and lipid metabolism have been observed in Alzheimer's disease [ 45 , 46 ] and FE65 is implicated in the pathogenesis of the disease [ 3 ], it is worthwhile to determine the roles of the ARF6-ARNO-FE65-ELMO1-DOCK180 multimeric complex in both physiological and pathological conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, the level of calcium transporter SERCA2 is increased in FE65/FE65L1 double KO mice which suggest a role of FE65 in calcium homeostasis [ 42 ]. On the other hand, both ARF6 signalling and FE65 have been associated with lipid metabolism through the regulation of lipid-modifying enzymes [ 43 , 44 ] and binding to the low-density lipoprotein receptor family proteins [ 3 ], respectively. As aberrant calcium homeostasis and lipid metabolism have been observed in Alzheimer's disease [ 45 , 46 ] and FE65 is implicated in the pathogenesis of the disease [ 3 ], it is worthwhile to determine the roles of the ARF6-ARNO-FE65-ELMO1-DOCK180 multimeric complex in both physiological and pathological conditions.…”
Section: Discussionmentioning
confidence: 99%
“…FE65, also known as amyloid precursor protein-binding family B member 1, is a 97 kDa brain-enriched adaptor protein with three distinct protein–protein interaction domains: a tryptophan–tryptophan (ww) domain and two successive phosphotyrosine-binding (ptb) domains. Using these domains, FE65 complexes with different interacting partners trigger various biological processes including the regulation of cytoskeleton dynamics [ 3 ]. We previously demonstrated that FE65 interacts with ARF6 via its PTB1 domain and potentiates ARF6-mediated neurite outgrowth [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Fe65 † APP, Mena Scaffolding protein that interacts with APP; indirectly induces actin polymerization through Mena (Augustin and Kins, 2021).…”
Section: Name Target Functionmentioning
confidence: 99%
“…Fe65, a scaffold protein family, interacts with and alters the processing of APP ( Augustin and Kins, 2021 ). Fe65 is mainly enriched in the brain, and its overexpression has been shown to reduce Aβ levels in AD model mice ( McLoughlin and Miller, 2008 ).…”
Section: Other Actin-associated Proteins Involved In Cytoskeletal Dys...mentioning
confidence: 99%
“…The crosstalk between LDL receptors and APP is even more complex if we look at another interactor known as FE65, a cytoplasmic adaptor protein [ 86 ]. In fact, LRP1, LRP8 and VLDLR bind to FE65, forming different tripartite complexes, which may modulate APP endocytic trafficking, Aβ production, APP intracellular domain (AICD) nuclear trafficking and DNA protection [ 85 , 87 ]. Notably, AICD, along with FE65 and Tip60/Kat5, a lysine acetyltransferase regulating hippocampal gene network linked to memory formation [ 88 ], associates into complexes in nuclear transcription factories, while the C-terminal portions of LDL receptors are recruited at a nuclear level upon gamma-secretase cleavage [ 67 , 89 ].…”
Section: Ldl Receptor Interactors In Normal and Pathological Brain Co...mentioning
confidence: 99%